Shifts in organizational form under a dual income tax system - Thor O. Thoresen; Annette Alstadsæter (Statistics Norway, Research Department, 2008)
Evidence of owners of small businesses engaging in tax motivated shifts in organizational form is scarce. The main reason is lack of micro data enabling us to track tax-payers' movements across organizational modes. By exploiting new panel data that combine information from several public registers, we observe Norwegian owners of small businesses and their organizational forms in the period from 1993 to 2003. Under the hypothesis that certain characteristics of the Norwegian dual income tax system encourage shifts into widely held corporations, we observe outcomes for different organizational form choices. We show that owners of small firms that became widely held corporations have higher income growth than those that remained in self-employment or as a closely held corporation.
Keywords: H25; L22; 330; income shifting; small businesses; organizational shifts; dual income tax